Analisis Efektivitas Magang pada Program Merdeka Belajar Kampus Merdeka di Seluruh Indonesia - Widiastu, Pari Mahayu; Katika, Lindawati (Universitas Negeri Padang, 2023)
Indonesia has an unemployment rate above the world average in the last five years (2017-2021). In Southeast Asia, Indonesia has the second highest unemployment rate after Brunei Darussalam. This needs to be given attention according to the Sustainable Development Goals (SDG) point 1